علاقة الري بمياه كبريتية مالحة و بعض الخصائص الفيزيائية والكيميائية للتربة في جاهزية البوتاسيوم لترب منطقة جبل الحص / حلب - الجردي أحمد; ترت محمد (Latakia University Journal -Biological Sciences Series, 2019)
تم اختيار خمسة مواقع تختلف باحتوائها على نسب مختلفة من الطين والبوتاسيوم لتقدير البوتاسيوم الذائب والمتبادل وغير المتبادل والمعدني والكلي فيها. أظهرت النتائج وجود علاقة طردية بين تناقص كمية البوتاسيوم المتبادل والذائب بانخفاض نسبة الطين وارتفاع نسبة الرمل، وعكسية مع نسبة الرمل بعامل ارتباط 48-93 %. تناقص محتوى البوتاسيوم المتبادل بتزايد بوتاسيوم مياه الري بعامل ارتباط 69-93 %، و تزايد محتوى البوتاسيوم الذائب بتزايد نسبة البوتاسيوم في مياه الري. أظهرت النتائج تناقص محتوى البوتاسيوم المتبادل والذائب بتزايد قيم SAR بعامل ارتباط 57-86 %، كما لوحظ وجود علاقات ارتباط موجبة ومعنوية بين البوتاسيوم المتبادل والذائب وبين البوتاسيوم المتبادل والطين والتوصيل الكهربائي موجبة وعالية المعنوية، وبالتالي فإن البوتاسيوم المتبادل والذائب سيزداد بازدياد قيم التوصيل الكهربائي لمستخلص التربة. Five sites were selected with different rates of clay and potassium. The results showed a direct correlation between the decrease in the amount of potassium dissolved and mutual with the low rate of clay and the high rate of sand and indirect relationship with the rate of sand by correlation factor about 48-93 %. Also the content of potassium mutual decreased with the increase of potassium of irrigation water by correlation factor about 69-93 % and increasing the content of potassium dissolved by increased the rate of potassium in irrigation water. As well as the results showed decreased content of potassium dissolved and mutual by increased the values by correlation factor from 57 to 86 %. It was also noted that there is a positive and moral relationship between potassium dissolved and mutual and between potassium mutual and clay and electrical conductivity that explains that the potassium dissolved and mutual will increase by increased the values of electrical conductivity of soil extract.